Thermal, Mechanical and Biocompatibility Analyses of Photochemically Polymerized PEGDA250 for Photopolymerization-Based Manufacturing Processes - Natalia Rekowska; Jennifer Huling; Andreas Brietzke; Daniela Arbeiter; Thomas Eickner; Jan Konasch; Alexander Riess; Robert Mau; Hermann Seitz; Niels Grabow; Michael Teske (MDPI AG, 2022)
Novel fabrication techniques based on photopolymerization enable the preparation of complex multi-material constructs for biomedical applications. This requires an understanding of the influence of the used reaction components on the properties of the generated copolymers. The identification of fundamental characteristics of these copolymers is necessary to evaluate their potential for biomaterial applications. Additionally, knowledge of the properties of the starting materials enables subsequent tailoring of the biomaterials to meet individual implantation needs. In our study, we have analyzed the biological, chemical, mechanical and thermal properties of photopolymerized poly(ethyleneglycol) diacrylate (PEGDA) and specific copolymers with different photoinitiator (PI) concentrations before and after applying a post treatment washing process. As comonomers, 1,3-butanediol diacrylate, pentaerythritol triacrylate and pentaerythritol tetraacrylate were used. The in vitro studies confirm the biocompatibility of all investigated copolymers. Uniaxial tensile tests show significantly lower tensile strength (82% decrease) and elongation at break (76% decrease) values for washed samples. Altered tensile strength is also observed for different PI concentrations: on average, 6.2 MPa for 1.25% PI and 3.1 MPa for 0.5% PI. The addition of comonomers lowers elongation at break on average by 45%. Moreover, our observations show glass transition temperatures (Tg) ranging from 27 °C to 56 °C, which significantly increase with higher comonomer content. These results confirm the ability to generate biocompatible PEGDA copolymers with specific thermal and mechanical properties. These can be considered as resins for various additive manufacturing-based applications to obtain personalized medical devices, such as drug delivery systems (DDS). Therefore, our study has advanced the understanding of PEGDA multi-materials and will contribute to the future development of tools ensuring safe and effective individual therapy for patients.